A checklist of species of the family Zoothamniidae (Ciliophora: Peritrichia), symbionts of crustaceans - Mayén-Estrada, Rosaura; Dias, Roberto Junio Pedroso (Zootaxa, 2021)
Eight genera are included in the family Zoothamniidae, and at the present the data of the epibiotic species on crustaceans is not updated. Thus, the main goal of the present work is to provide the checklist of zoothamniids worldwide reported as associated to several groups of crustaceans, including some data of their geographic distribution, and also to provide the complete list of species of this peritrich group. We obtained all available data of family Zoothamniidae and checked their taxonomic status. Then we provided the complete list of species including those reported as epibionts on crustacean hosts. We obtained 156 species included in eight genera of Zoothamniidae, being 85 species recorded as symbionts on 86 species of hosts. Genus Zoothamnium contained the higher number (56) of epibiotic species on crustaceans, and genus Pseudohaplocaulus has not been reported for any crustacean. The reviewed data highlights the concentration of records in Europe, and stands out the need to amplify sampling and studies in the Southern Hemisphere. The main groups of crustaceans infested by zoothamniids are the amphipods, isopods and decapods.